Character Education in Panca Sani Pependetan Dance Creation - Ni Wayan Iriani; Ni Wayan Mudiasih (Mudra Jurnal Seni Budaya, 2023)
The pependetan dance "Panca Sani" is a creative dance whose movements are based on a developed traditional dance. This dance describes the reception and expression of gratitude to the gods who descend into the natural world. The idea for this work was inspired by the Wayang Istri dance at the Pangrebongan Kesiman temple. Wayang Istri dance is a ngerebong traditional dance of the Kesiman people held at the Agung Petikan Pengarebongan Kesiman Temple, Denpasar. This ceremonial dance is held every 6 months and falls on Buda Cemeng Langkir Day. The movements and costumes are presented very simply by bringing a property of a rectangular shape made of cow/buffalo leather. The method of creating the "Panca Sani" Pependetan dance refers to I Wayan Dibia's concept in the Panca Sthiti Ngawi Sani creation methodology through five stages of the art creation process, as follows: inspiration/ngawirasa, exploration/ngawacak, conception/ngarencana, execution/ngawangun and the production/ngebah stage. 5 female dancers dance this Pependetan creative dance to express the characters in the dance: majesty, nobility, sincerity which is presented through the graceful beauty of the movements, and the costumes. The dance accompaniment uses a set of Gong Gede gamelan. Pependetan dance is a character education effort with the community to foster a conducive mood and moral formation for each individual involved in the world of education. Growing individuals as moral persons according to what is desired is the core of character education. The results of this work are expected to preserve the teaching and development of pependetan to form a positive attitude for the formation of good character.